Exploring scholarly perceptions of preprint servers - Shir Aviv-Reuven; Jenny Bronstein; Ariel Rosenfeld (Information Research: An International Electronic Journal)
Introduction. Preprint servers play an important role in scholarly communication.  The study investigates scholars’ engagement, experiences, and perceptions regarding the use of these servers, both as information sources and publishing venues This qualitative study seeks to extend our understanding of how these servers operate within the academic ecosystem and influence scholarly communication.